The effect of counseling based on the model of continuous care led- midwife on nausea and vomiting during pregnancy in patient referred to comprehensive health centers in Hamadan, 2020 - Azadeh Aazadi Moghtader; Seyedeh Zahra Masoumi; Batul Khodakarami; Ghodratollah Roshanaei; Parisa Parsa (Hamadan University of Medical Sciences, 2022)
Background and Objective: Nausea and vomiting during pregnancy are one of the most common complaints of pregnant women. The present study aimed to assess the effect of counseling based on the model of continuous midwife-led care on nausea and vomiting during pregnancy. Materials and Methods: This two-group clinical trial study was performed on 60 pregnant women aged 8-12 weeks in 2020. Participants in the intervention group received three face-to-face counseling sessions based on the continuous midwife-led care model, while the control group received routine prenatal care. The severity of nausea and vomiting was assessed using the Pregnancy-Unique Quantification of Emesis (PUQE) questionnaire three days before the commencement of the study and two weeks during the study. Data analysis was performed in SPSS software (version 22) using the Chi-square test, one-way analysis of variance, and analysis of covariance. A p-value less than 0.05 was considered statistically significant. Results: In the intervention group, after the midwife-led consultation, compared to before, the mean scores of nausea and vomiting, as well as the overall severity of nausea and vomiting, decreased during two weeks (P<0.001). Although this decrease was not significant in the first week of the intervention compared to the control group (P>0.05), the difference between the two groups in the second week of the study was significant in terms of overall severity of nausea and vomiting based on the overall score of the PUQE questionnaire (P <0.05). Conclusion: As evidenced by the obtained results, the use of the model of continuous midwife-led care is recommended to reduce nausea and vomiting during pregnancy.